2011
DOI: 10.1007/s00468-011-0659-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural evaluations of zygotic embryos and seedlings of the macaw palm (Acrocomia aculeata, Arecaceae) during in vitro germination

Abstract: Acrocomia aculeata is an oil producing tropical palm tree with exceptional potential for producing biofuel.As the propagation of this species is often difficult because of its pronounced seed dormancy, the present work examined the morphology and the anatomy of zygotic embryos and seedlings during in vitro germination. Embryos were put in MS media supplemented with organic compounds and cultivated in the dark at 30°C for 20 days. The dry weights, lengths, and diameters of the cotyledonary petioles, haustoria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 31 publications
(54 reference statements)
0
39
0
4
Order By: Relevance
“…In vitro zygotic embryo culture has been used as an alternative for swift propagation, and among other applications, the method has been used to investigate dormancy caused by embryo immaturity or by the presence of germination inhibitors in the endosperm, in order to study the nutritional and physiologic aspects of embryonic development (Anjun, 2014;Medeiros et al, 2015). Thus, palm embryo culture allows for the assessment of seed physiology, development, and germination (Ribeiro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro zygotic embryo culture has been used as an alternative for swift propagation, and among other applications, the method has been used to investigate dormancy caused by embryo immaturity or by the presence of germination inhibitors in the endosperm, in order to study the nutritional and physiologic aspects of embryonic development (Anjun, 2014;Medeiros et al, 2015). Thus, palm embryo culture allows for the assessment of seed physiology, development, and germination (Ribeiro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Presently the production of A. aculeata is primarily extractive and its propagation done with seeds, which exhibit dormancy and experience a low germination rate (Lorenzi 2006;Ribeiro et al 2012), although Motoike et al (2007) developed a method that raised the germination rate to 60-80%. For large-scale commercial use of A. aculeata it is necessary to develop a technique for the clonal propagation in order to establish a uniform cultivation system.…”
Section: Introductionmentioning
confidence: 99%
“…The family Arecaceae demonstrates morphological dormancy associated with embryo immaturity (Baskin and Baskin , Orozco‐Segovia et al , Perez et al ). Recent work with macaw palm seeds (Ribeiro et al , , ) and other palms species from Cerrado biome (Neves et al , Magalhães et al , Oliveira et al ), has however demonstrated that their dormancy is of the physiological non‐profound type ( sensu Baskin and Baskin ) and is related to the incapacity of the embryo to overcome the resistance of the operculum (a structure formed by the opercular tegument and micropylar endosperm). While physiological dormancy is known to be strongly controlled by alterations in the hormonal profile of seeds (Kucera et al , Nonogaki et al ), studies on this issue in palms have been restricted to a single study in Elaeis guineensis Jacq.…”
Section: Introductionmentioning
confidence: 99%